Why Do Unemployed Americans Blame Themselves While Israelis Blame the System? - Sharone, Ofer (Social Forces, 2013)
This article provides a new account of American job seekers' individualized understandings of their labor-market difficulties, and more broadly, of how structural conditions shape subjective responses. Unemployed white-collar workers in the U.S. tend to interpret their labor market difficulties as reflecting flaws in themselves, while Israelis tend to perceive flaws in the hiring system. These different responses have profound individual and societal implications. Drawing on in-depth interviews with unemployed job seekers and participant observations at support groups in the U.S. and Israel, this article shows how different labor market institutions give rise to distinct job search games, which I call the chemistry game in the U.S. and the specs game in Israel. Challenging the broad cultural explanations of the unemployment experience in the existing literature, this article shows how subjective responses to unemployment are generated by the search experiences associated with institutionally rooted job search games.